The effect of dietary adaption on cranial morphological integration in capuchins (order Primates, genus Cebus). - Jana Makedonska (Public Library of Science (PLoS), 2012)
A fundamental challenge of morphology is to identify the underlying evolutionary and developmental mechanisms leading to correlated phenotypic characters. Patterns and magnitudes of morphological integration and their association with environmental variables are essential for understanding the evolution of complex phenotypes, yet the nature of the relevant selective pressures remains poorly understood. In this study, the adaptive significance of morphological integration was evaluated through the association between feeding mechanics, ingestive behavior and craniofacial variation. Five capuchin species were examined, Cebus apella sensu stricto, Cebus libidinosus, Cebus nigritus, Cebus olivaceus and Cebus albifrons. Twenty three-dimensional landmarks were chosen to sample facial regions experiencing high strains during feeding, characteristics affecting muscular mechanical advantage and basicranial regions. Integration structure and magnitude between and within the oral and zygomatic subunits, between and within blocks maximizing modularity and within the face, the basicranium and the cranium were examined using partial-least squares, eigenvalue variance, integration indices compared inter-specifically at a common level of sampled population variance and cluster analyses. Results are consistent with previous findings reporting a relative constancy of facial and cranial correlation patterns across mammals, while covariance magnitudes vary. Results further suggest that food material properties structure integration among functionally-linked facial elements and possibly integration between the face and the basicranium. Hard-object-feeding capuchins, especially C. apella s.s., whose faces experience particularly high biomechanical loads are characterized by higher facial and cranial integration especially compared to C. albifrons, likely because morphotypes compromising feeding performance are selected against in species relying on obdurate fallback foods. This is the first study to report a link between food material properties and facial and cranial integration. Furthermore, results do not identify the consistent presence of cranial modules yielding support to suggestions that despite the distinct embryological imprints of its elements the cranium of placental mammals is not characterized by a modular architecture.